Effect of Topical Beclomethasone on Inflammatory Markers in Adults with Eosinophilic Esophagitis: A Pilot Study. Issue 2 (June 2017) - Bhardwaj, Neeti; Ishmael, Faoud; Lehman, Erik; Bethards, Deborah; Ruggiero, Francesca; Ghaffari, Gisoo
Background: Topical corticosteroids have proven efficacy in the treatment of eosinophilic esophagitis (EoE) and are considered the cornerstone of therapy. Objective: To evaluate the effect of topical beclomethasone dipropionate (BDP) therapy on clinical outcomes, esophageal eosinophilia, and other markers of inflammation in patients with EoE. Methods: Nine subjects with a biopsy-proven diagnosis of EoE were enrolled. In a cross-over design, the subjects were randomly assigned to a sequence of BDP and placebo. Treatment periods were 8 weeks, with a 4-week washout period. The subjects had endoscopic biopsies and blood tests at baseline and after each treatment period. They were instructed to maintain a diary of symptoms. Immuno-histochemical studies were performed for interleukins IL-4, IL-5, IL-13, granulocyte-macrophage colony-stimulating factor (GM-CSF), and transforming growth factor (TGF) beta. Reverse transcription polymerase chain reaction was performed for IL-3, IL-4, IL-5, IL-10, IL-13, IL-17F, IL-25, IL-33, chemokine ligands (CCL)2, CCL5, CCL11, GM-CSF, and TGF-beta levels. The mast cell tryptase (MCT) level was measured in esophageal tissues. Results: BDP led to a significantly larger decrease in esophageal eosinophilia compared with placebo, but there was no significant change in peripheral eosinophilia and high-sensitivity C-reactive protein between the two groups. The study was not powered enough for us to report a significant improvement in clinical symptoms. There was a significant decrease in tissue IL-13 and MCT levels from baseline to the end of treatment between the treatment and placebo groups. Mean fold decreases in cytokine expression between the baseline and treatment groups were observed for IL-17F, IL-25, CCL2, and CCL5. Conclusion: Treatment with topical BDP was associated with significant decrease in esophageal eosinophilia, MCT and IL-13. BDP is a potential alternative to fluticasone propionate and budesonide for treatment of EoE. Larger studies are needed to validate these findings.